2019
DOI: 10.3390/ijms20153825
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy as a Tool for Differentiation of Leiomyomas and Sarcomas of Corpus Uteri

Abstract: Utilization of liquid biopsy in the management of cancerous diseases is becoming more attractive. This method can overcome typical limitations of tissue biopsies, especially invasiveness, no repeatability, and the inability to monitor responses to medication during treatment as well as condition during follow-up. Liquid biopsy also provides greater possibility of early prediction of cancer presence. Corpus uteri mesenchymal tumors are comprised of benign variants, which are mostly leiomyomas, but also a hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 191 publications
(297 reference statements)
0
12
0
2
Order By: Relevance
“…Dvorska et al (2019) [118] found it intriguing that there is no great interest in developing good quality techniques that could differentiate benign UFs and malignant LMSs. The main reason could be related to the very low incidence of these malignant lesions [118].…”
Section: Different Mirnas In the Differential Diagnosis Of Uterine Fimentioning
confidence: 99%
See 1 more Smart Citation
“…Dvorska et al (2019) [118] found it intriguing that there is no great interest in developing good quality techniques that could differentiate benign UFs and malignant LMSs. The main reason could be related to the very low incidence of these malignant lesions [118].…”
Section: Different Mirnas In the Differential Diagnosis Of Uterine Fimentioning
confidence: 99%
“…Dvorska et al (2019) [118] found it intriguing that there is no great interest in developing good quality techniques that could differentiate benign UFs and malignant LMSs. The main reason could be related to the very low incidence of these malignant lesions [118]. Nowadays, one of the biggest concerns for surgeons operating on women with UFs is the potential intra-operative fragmentation of LMS during laparoscopic surgery, which may cause intraabdominal spread of malignant cells [119].…”
Section: Different Mirnas In the Differential Diagnosis Of Uterine Fimentioning
confidence: 99%
“…Accurate identification and classification are crucial for successful treatment as responses to specific therapies vary widely among tumor types of different origin and misdiagnosis may lead to poor treatment outcomes ( 5 ). However, due to overlap in histopathological features among sarcoma and the existence of multiple subtypes or variations in a single histology, pathologists and clinicians increasingly rely on molecular diagnostic methods ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue contains eight original research studies [20,21,22,23,24,25,26,27], and five review papers [28,29,30,31,32]; the diversity of the papers demonstrates how many different topics are covered by cell-free nucleic acid research.…”
mentioning
confidence: 99%
“…Dvorska et al reviewed the utility of liquid biopsy as a tool for the differentiation of leiomyomas and sarcomas of corpus uteri [30]. They collected the most important knowledge of mesenchymal uterine tumors and showed the benefits of liquid biopsy [30].…”
mentioning
confidence: 99%